The effect of organic fertilizers on the leaf morphology and stomatal density of Pogostemon cablin Benth - MEUTIA ZAHARA; SUWARNIATI SUWARNIATI; QURRATU AINI; MUSLIM MUSLIM (Jurnal Natural, 2021)
Pogostemon cablin Benth is one of the most important crops grown in Indonesia, especially in Aceh province. It is well known as Patchouli belongs to Lamiaceae family and shows a great demand for perfume, luxury products, food and beverage industry. This study conducted to determine the effect of organic fertilizers application on the leaf morphology and stomatal density on the Pogostemon cablin Benth. The seedlings were transplanted for three months on the soil mixed either with manure or compost. The results obtained that was no significant different in affecting the leaf morphology of Pogostemon cablin Benth. The treatment with manure application showed the highest leaf length (15.23 cm) and the highest leaf width (10.5 cm), the leaf color is green. While the stomatal density obtained the significant difference among the treatments, the highest stomatal density in both side of the leaf surface showed in the application of manure, 663.5 mm-2 for adaxial part and 486.38 mm-2 for abaxial part. Stomatal type is anisocytic and on the leaf surface was found glandular and non-glandular trichomes.